Analisis Kualitas Pelayanan, Kecerdasan Intelektual dan Fasilitas Terhadap Kepuasan Anggota pada KSPPS BMT Sejahtera Mandiri Tirtomoyo - Ismi Munfarida; Agus Suyatno; Esti Dwi Rahmawati (Jurnal Manajemen Bisnis Era Digital, 2024)
This research discusses the influence of service quality, and facilities on member satisfaction. The type of research used is quantitative research with data collection techniques using questionnaires. The population in this research is the members of KSPPS BMT Sejahtera Mandiri who are still actively making savings, totaling 77 respondents. The results of this research show that: 1) the service quality variable (X1) has a positive and significant effect on member satisfaction (Y). 2) the facility variable (X2) has a positive and significant effect on member satisfaction (Y). 3) the variables of service quality (X1), and facilities (X2) simultaneously influence member satisfaction (Y).